Inguinal Gravid Hysterocele in Feline - Costa, Rebeca dos Santos; Gomes Junior, Deusdete Conceição; Santos, Aline da Trindade Quintela; Neto, João Moreira da Costa; dos Santos, Levi Oliveira; Schaffer, Débora Passos Hinojosa; Neto, Egberto de Almeida Cardoso; Maciel, Milena de Almeida Pinheiro Cardoso (Acta Scientiae Veterinariae, 2017)
Background: Hysterocele is an inheritance rare in feline, characterized by the protrusion of the uterus by the inguinal channel, a situation related with the congenital abnormality of the inguinal ring, allowing the protrusion of abdominal contents for the subcutaneous space. As differential diagnosis of hysterocele are the breast cancer, abscesses and bruises and image exams such as radiography and ultrasonography have large relevance for identifying the disease and, additionally, clarify the hernia content. The purpose of this study was to describe one case report of the inguinal gravid hysterocele in a cat. Case: A 1-year-old female feline, without history of trauma of increase of volume in the inguinal region was referred for clinical evaluation. Due to the presence of three gestational vesicles, the decision by following-up the fetal development was taken, by means of periodical ultrasound evaluations, for performing operative procedure. At 56 days of gestation, when intestinal peristaltic movements of the three kittens were observed, cesarean was indicated. The procedure began by an oblique incision in the left retro-umbilical region, however, due to adhesions, there was no proper uterine exposition for hysterotomy. Retro-umbilical celiotomy, adhesiolise and return of the uterus for the abdominal cavity were performed in order to execute the cesarean followed by ovariohysterectomy. The hernial ring was debrided and sutured in order to keep patent the inguinal ring. No post-operatory complications were noted indicating that the established conduct allowed the survival of the parturient and its kittens. Discussion: In a casuistic study where data from 1988 until 2007 were collected, from the Faculty of Veterinary Medicine from the University of São Paulo, a higher occurrence of inguinal hernias was observed in female dogs, when compared with male dogs and, until that period, the inguinal hernia was not reported in the feline species. It is known that the inguinal ring may dilate with the obesity and increase of the intra-abdominal pressure, linked with the weakening of the adjacent structures. Besides, the appearance of hysterocele in females is also related with the estrus or gestation, caused by the hormonal imbalance, leading to the weakening of the conjunctive tissue, resulting in the enlargement of the inguinal rings, which is according to what was observed in this report where the animal was pregnant. Additionally, the application of contraceptive (progestin’s) could have accentuated the muscle fragility, favoring the projection of the uterus by the inguinal ring. In most of the cases described in literature, animals have no discomfort to the handling of the herniated content however, for some authors, the prolongation of surgical resolution may aggravate the clinical condition, predisposing the formation of adherences that may cause discomfort or pain, particularly when the bladder or intestinal loops are involved, resulting in difficulty urinating and defecating, respectively. Care must be taken during the reduction of the inguinal ring, in order to avoid compromising the external pudendal artery and vein, and of the genito-femoral nerve, which emerge from the tail-medial aspect of the ring. In this study, it was tried to perform the hernia suture in a way that the inguinal ring remained patent. On the same way that was performed in this study recommend the execution of ovariohysterectomy in order to avoid relapse and because it is an hereditary condition. The inguinal gravid hysterocele in feline may be adequately manage until the ideal moment for cesarean without prejudice to the parturient and to its products.